2007
DOI: 10.1590/s1516-80342007000100009
|View full text |Cite
|
Sign up to set email alerts
|

Características fonológicas de crianças com transtorno fonológico com e sem histórico de otite média

Abstract: RESUMO INTRODUÇÃOO transtorno fonológico é definido como uma alteração encontrada no sistema fonológico de um indivíduo e pode ser caracterizado por: substituições, omissões e ou distorções dos sons da fala. Essas alterações podem estar relacionadas às dificuldades com a organização das regras fonológicas da língua o que caracterizaria uma dificuldade cognitivo-lingüística, com a percepção auditiva dos sons e/ou com a produção dos mesmos (1-2) .Há que se considerar que a fonologia envolve um repertório de fone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2
56

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 18 publications
3
29
2
56
Order By: Relevance
“…highlight the gliding of liquids phonemes, cluster reduction and final consonant deletion , which are also highlighted in other studies [18][19][20][21] . These processes have a higher prevalence in children with disorders in phonological abilities.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…highlight the gliding of liquids phonemes, cluster reduction and final consonant deletion , which are also highlighted in other studies [18][19][20][21] . These processes have a higher prevalence in children with disorders in phonological abilities.…”
Section: Resultssupporting
confidence: 75%
“…Studies that investigated the abilities and disorders of language in children, who stutter, indicated that this group compared with those who do not stutter, had presented lower scores on several indices of receptive and expressive language [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] .…”
Section: Methodsmentioning
confidence: 99%
“…Valquíria Conceição Souza (1) , Jordana Siuves Dourado (2) , Stela Maris Aguiar Lemos (3) (1) Universidade Federal de Minas Gerais-UFMG -Belo Horizonte, MG, Brasil. (2) Hospital da Clínicas da Universidade Federal de Minas Gerais-UFMG -Belo Horizonte, MG, Brasil.…”
Section: Phonology Auditory Processing and Childhood Education: Enviunclassified
“…The phoneme is the smallest linguistic unit, simpler and more unique representative sound of the languages. Phonology is a component of the language that manages the repertoire of phonemes and organizes the way they are produced 2,3 . Throughout their development, the children learn to ignore some phonemes and keep attention to those that are most used in their mother tongue 4 .…”
Section: Conflict Of Interest: Non-existentmentioning
confidence: 99%
“…Outros estudos realizados com crianças brasileiras também mostram que a busca por tratamento fonoaudiológico ocorre principalmente entre cinco e oito anos (Salvatti et al, 2000;Wertzner et al, 2007b (2000), Wertzner (2002, Pagan (2003), Papp (2003), Papp e Wertzner (2006), Wertzner et al (2006Wertzner et al ( , 2007b.…”
Section: Ce X Processos Fonológicosunclassified